Characteristic points of Auckland commercial property cycles. Issue 5 (12th June 2019) - Szweizer, Moshe
Abstract : Purpose: The purpose of this paper is to expand our understanding of processes governing commercial property cycles, and to provide tools, which enable identification of property cycles' turning points' location. Design/methodology/approach: This paper is divided into three parts. The first looks at the demand-supply dynamics and the location of two characteristic cyclic points, the market bottom and the cycle commencement. In the second part a property relevant formula for entropy is derived, and its relation to the cycle overheated stage and the market peak is studied. In the third part, we discuss still another characteristic point of the cycle, which relates to the stage when developers elect to undertake new projects. This analysis is done by employing the chaos theory, and its relation to the cyclic evolution. Findings: It is found that some markets cycle, while others fluctuate only. A clear method for distinguishing among these is provided. The bottom of a cycle may overlap or be time separated from the start of a subsequent cycle. Market peaks are characterised by a sharp decrease in financial component to entropy for top quality building grades. A cycling market is characterised by crossing of a distinct vacancy rate during the cycle progression. Practical implications: The tools developed in the paper allow for clear characterisation of the market types and their cyclic behaviour. This in turn allows for timely characterisation of the market state and for short time-frame forecasting. The depth of a cycle may be calculated and the subsequent correction level estimated. Originality/value: The paper utilises cross-field approach by taking methods from both physics and mathematics and applying them to property markets. It breaks new ground both in property research and in applied mathematics by showing how the current frontier in pure mathematics may be applied to property.